PENGEMBANGAN MEDIA AUDIO VISUAL TENTANG PRAKTIKUM REAKSI OKSIDASI REDUKSI DAN ELEKTROKIMIA SEBAGAI MEDIA PEMBELAJARAN MANDIRI BAGI SISWA SMA/ MA KELAS XII SEMESTER 1 - Anjar Purba Asmara; Agus Dwi Ananto; Nokman Riyanto (Lantanida Journal, 2014)
The research is aimed to develop media of chemistry learning which based on technolgy and information esspecially for student of SMA/ MA grade XII semester I and to determine the value of quality of the media by scoring from chemistry teacher in SMA Yogyakarta Regency. The process of developing media through reviewing by learning media expert and also by peer reviewer. The instument for evaluating to the media is questioner which containing several aspects and criteria of evaluation and scoring. The scoring had done by five chemistry teachers of SMA/ MA in Yogyakarta Regency. There are eight aspects of evaluation and scoring with thirty six indicator of scoring items. The form of the result of evaluation is qualitative data that must be converted into quantitative data for determining of the media’s quality. The product of the research is media audio visual for practicum of oxidation reduction reaction and electrochemistry for student of SMA grade XII semester 1. The components of the product are using guidance to the media, student activity part, evaluation part, the answer of student activity, and also the profile of the researcher. Based on evaluation and scoring from the teachers, the media is reached level of quality as very good level with average score as much as 145.52 where the ideal score is 144. Based on the research, the media could be used to help student to learn chemistry in SMA/MA grade XII semester 1 chapter oxidation and reduction reaction and electrochemistry